Post-bariatric abdominoplasty: our experience - Grignaffini, Eugenio; Grieco, Michele P.; Bertozzi, Nicolo'; Gandolfi, Marco; Palli, Dante; Cinieri, Francesco Giovanni; Gardani, Marco; Raposio, Edoardo (Acta Biomedica Atenei Parmensis, 2015)
The fast increase in obesity has been followed by the growth in the demand for plastic surgery in formerly obese patients. The weight loss is accompanied by new dysfunctions and disorders of the outline of the body that affects the quality of life of the patient. Abdominoplasty is a cosmetic surgery procedure that aims to remove the excess of skin and the redundant fat. The aim of this paper was to analyze our experience in this field and to test how functional abdominoplasty improved quality of life in the operated patients. In our Unit from January 2012 to December 2014, 25 patients (18 women and 7 men, age: 24 - 79 years, mean: 51 years) underwent abdominoplastic surgery. Only at least six months after bariatric surgery the patients were eligible for functional abdominoplasty. Average weight of the patients before surgery was 83.5 kg (range 58 - 163 Kg); averege BMI was 31 (range 24.77 - 57). The average quantity of tissue removed was 1.765 Kg (range 250 g - 11,5 Kg). Minor complications rate was in agreement with the percentages reported in literature. No mortality and major complications have occurred in our series. The majority of patients undergoing post-bariatric abdominoplasty reported an improvement in the quality of life and psychological well-being. In our opinion, however, only a multidisciplinary (surgical, psychological, dietological) approach of the post-bariatric patient allows to maintain long-term aesthetic and functional results.